1984
DOI: 10.1002/chin.198414182
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF 4‐PENTEN‐4‐OLIDES (Γ‐METHYLENE‐Γ‐BUTYROLACTONES) VIA 4‐PENTENOIC ACIDS

Abstract: Säurekatalysierte Kondensation der Allylalkohole (I) mit den Orthoestern (II) und Orthoester‐Umlagerung nach Claisen liefern Gemische der entsprechenden Pentensäureethyl‐ und ‐allylester, die ohne Isolierung zu" den Pentensäuren (III) verseift werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Snider and Johnston investigated the halolactonizations of γ,δ-unsaturated acids and found that the reaction using NBS in a mixture of THF and acetic acid or bromine in methanol produces a mixture of γ-lactone and δ-lactone. 1760 There are a few other reagent combinations for the bromolactonization reaction using NBS, which include examples such as NBS/ AcOH−THF−H 2 O, 1761,1762 1765 Yeung has shown another catalytic bromolactonization of long-chain olefinic acids using NBS using a zwitterionic catalyst. 1766 This work resulted in an efficient synthetic route for medium-sized lactones.…”
Section: Use Of Nbs In Cyclization Reactionsmentioning
confidence: 99%
“…Snider and Johnston investigated the halolactonizations of γ,δ-unsaturated acids and found that the reaction using NBS in a mixture of THF and acetic acid or bromine in methanol produces a mixture of γ-lactone and δ-lactone. 1760 There are a few other reagent combinations for the bromolactonization reaction using NBS, which include examples such as NBS/ AcOH−THF−H 2 O, 1761,1762 1765 Yeung has shown another catalytic bromolactonization of long-chain olefinic acids using NBS using a zwitterionic catalyst. 1766 This work resulted in an efficient synthetic route for medium-sized lactones.…”
Section: Use Of Nbs In Cyclization Reactionsmentioning
confidence: 99%
“…Essentially, iodination of the acid gave 5-iodomethyl-dihydrofuran-2-one in excellent yield. Subsequent elimination with 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) gave γ -angelicalactone in moderate yield (Gunther et al, 1984). 3-Methyl-5-methylene-dihydro-furan-2-one was obtained in excellent yield using the same method with 2-methylpenten-4-enoic acid as the starting material (Gunther et al, 1984).…”
Section: Synthesis Of Commercially Unavailable Chemicalsmentioning
confidence: 99%
“…Essentially, iodination of the acid gave 5-iodomethyl-dihydrofuran-2-one in excellent yield. Subsequent elimination with 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) gave γangelicalactone in moderate yield (Gunther et al, 1984). 3-Methyl-5-methylene-dihydro-furan-2-one was obtained in excellent yield using the same method with 2-methylpenten-4-enoic acid as the starting material (Gunther et al, 1984).…”
Section: Synthesis Of Commercially Unavailable Chemicalsmentioning
confidence: 99%